Clinical characteristics of patients with granulomatous lobular mastitis associated with Corynebacterium parakroppenstedtii infection and drug sensitivity analysis of the isolated strains - Yifei Zeng; Mengjie Wang; Xiang Gao; Dongxiao Zhang; Na Fu; Wenjie Zhao; Qiao Huang (BMC, 2024)
Abstract Background It is presently considered that Corynebacterium especially Corynebacterium kroppenstedtii (CK) infection, is one of the important causes of granulomatous lobular mastitis (GLM). However, the pathogen of mastitis in the past two years has been identified as a newly discovered Corynebacterium. But it is unclear whether the pathogen associated with the occurrence of GLM is also this bacterium. Methods GLM female patients with positive bacterial culture in pus specimens from February 2023 to February 2024 who were identified as CK infection by mass spectrometer were selected as the research objects in this study, and the clinical isolates were identified by 16S rDNA sequencing technology to identify the specific pathogen of GLM-related bacterial infection. Subsequently, the clinical characteristics of the patients were compared with those of GLM patients without bacterial infection during the same period, to explore the effect of this particular type of Corynebacterium infection on disease development in GLM patients. Finally, we tested the minimum inhibitory concentration (MIC) values of antibiotics when inhibiting these separation strains in vitro through the E-Test experiment, to evaluate their medicine sensitivity. Results A total of 31 GLM patients initially diagnosed with Corynebacterium kroppenstedtii (CK) infection via MALDI-TOF MS were enrolled in the study. However, subsequent 16S rDNA sequencing revealed that 28 isolates (90.32%) were actually identified as the newly recognized Corynebacterium parakroppenstedtii (CPK). This discovery challenges the conventional belief that CK is the primary pathogen of GLM, suggesting instead that CPK is the predominant pathogen associated with GLM bacterial infections. Comparative analysis of the clinical characteristics between the two groups revealed a significantly higher recurrence rate among CPK-infected GLM patients compared to those without CPK infection, along with elevated prolactin levels (P < 0.05). The sensitivity test results indicated high sensitivity of the isolates to vancomycin, linezolid, and rifampicin. Conclusion In conclusion, this study highlights that Corynebacterium kroppenstedtii strains isolated from GLM specimens were Corynebacterium parakroppenstedtii, serving as the primary pathogen closely linked to GLM's occurrence. CPK infection significantly increases the risk of recurrence in GLM patients, with elevated prolactin levels potentially playing a pivotal role in this process. In clinical antimicrobial treatment, antimicrobials other than penicillin and ciprofloxacin may be empirically administered when sensitivity test results are inconclusive.